(untitled) (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2020)
A human resource (HR) information system is essentially an intersection of human resources and information technology through HR software. A manual system is a system where data/information is recorded without using a computer system, but it can take longer than expected. In this research, the researcher will indicate the importance of having a HR information system focusing on recruitment and how it will make one’s work easily by typing and saving it in the database. The proponents started the project by finding the client that will entertain and will give the information they need for system development. Second, they looked for a company that is suitable for the system project. The proponents asked their research adviser for the requirements needed for the interview. The researchers used the data they gained from the client as a basis for their system development process. Lastly, after analyzing the data they gathered, the researchers started working on their documents. The client gave information about the problems that they faced due to the lack of a computerized system. The researchers built this system for the client to provide a modern and upgraded computerized system for the easy process of their recruitment. The researchers also encountered some problems that our client is currently facing because of this fast modernization; being late to trends is not bad, but being updated especially in technology will serve us a wide range of new knowledge and make our everyday lives easier. In this project, the proponents will surely meet the satisfaction of their clients and assure them that this system will be helpful and usable to the organization of our clients. The use of a login system will give your employees’ information high-level security to avoid data mining and the usage of this system by an unauthorized person. You can also track the employees’ requirements through the use of our system, which may help the user monitor their employees. The use of a recruitment module in our system will help the user to deploy their pending employees to their desired department inside the school. The result showed how modern technology can help us be updated on what is trending and new. Our project system is designed to be a user-friendly system for the HR staff of the school. This system can satisfy the user.